Activity of platinum and cetuximab in cutaneous squamous cell cancer not amenable to curative treatment - Donata Galbiati; Stefano Cavalieri; Salvatore Alfieri; Carlo Resteghini; Cristiana Bergamini; Ester Orlandi; Francesca Platini; Laura Locati; Luca Giacomelli; Lisa Licitra; Paolo Bossi (BioExcel Publishing Ltd, 2019)
Background: Unresectable or metastatic cutaneous squamous cell cancers (cSCCs) are rare but potentially life-threatening diseases. In this setting, systemic therapy has a palliative intent with limited benefit, but there is no established consensus regarding the proper management of this tumour. This retrospective study aimed to review outcomes in patients with non-curable cSCC treated with platinum-based chemotherapy and cetuximab. Methods: We considered 12 consecutive patients treated between June 2010 and March 2016. All patients had received previous treatment for the local disease. Results: The overall response rate was 50%, and the disease control rate was 67%. Median progression-free survival and overall survival were 6.6 (95% confidence interval [CI]: 1.9-8.4) and 14.6 (95% CI: 9.4-20.1) months, respectively. The median duration of response was 4.8 months (95% CI: 1.2-5.9). The most frequent toxicities were skin reactions (58%; grade 3: 25%) and anaemia (10%). No grade 4 toxicities were observed. Conclusions: Cetuximab and platinum-based chemotherapy were shown to be feasible and active in cSCC, with an acceptable toxicity profile, even if with a limited duration of response.